The effect of group exercises combined with repetitive training methods on developing speed endurance in under-21 football players - Asleawa, Wesam; Shihab, Sabreen (Journal of Physical Education, 2025)
This study aimed to identify the effect of group exercises using repetitive training on the speed endurance of under-21 football players. The researcher used a set of group exercises on a sample of 32 under-21 players from the Electrical Industries Club, with a mean age of 20.4. The players were divided into two groups, an experimental group and a control group, each consisting of 14 players. A comparison was then conducted between the two groups to ensure the validity of the starting line. The exercises were then implemented with two training sessions per week, totaling eight training sessions over a month. These exercises were applied to the players during their special preparation phase. After conducting the main experiment and performing the post-test of speed endurance, and comparing the results of the pre-test and post-test, the study found significant results in the speed endurance of the experimental group players, who outperformed the control group in the post-test. This is attributed by the researcher to the effect of the independent variable, which is the group exercises using repetitive training. Furthermore, the researcher recommends The researcher believes that the training curricula for coaches in the special preparation stages should include exercises specifically designed to develop physical capabilities, and that these exercises should be standardized, especially speed endurance, and also that similar research should be conducted within the framework of comparing the capabilities of players with other physical capabilities.